Particular Solutions of the Radial Schrodinger Equation via Nabla Discrete Fractional Calculus Operator - Ozturk, Okkes; Yilmazer, Resat (Amer Inst Physics, 2017)
One of the most popular research interests of science and engineering is the fractional calculus theory in recent times. Discrete fractional calculus (DFC) has also an important position in the fractional calculus. The nabla operator in DFC is practical for the singular differential equations. The purpose of this study is to obtain particular solutions of the radial Schrodinger equation (that is, the most important equation of quantum physics) via nabla DFC operator. These solutions were obtained in the forms of discrete fractional.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 19-25, 2016 -- Rhodes, GREECE